Revolusi Pembangunan Kota: Dampak Aplikasi SIMBG Terhadap Kepuasan Pemohon Izin Bangunan Gedung - Pulungan, Datuk Tua; Khadavi, Khadavi; Peli, Martalius (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
Building Construction Management is the implementation of laws and government regulations that signal to the entire community wishing to apply for building permits. Thus, the manual system that has been in place is replaced by a digital system through the SIMBG application in order to provide efficiency and satisfaction to the community in applying for building permits. This study aims to determine the influence of service quality on the satisfaction of Building Permit Applicants (PBG) on the Building Management Information System (SIMBG) application, and the usefulness of the SIMBG application with the satisfaction of PBG applicants implemented in Padangsidimpuan City. The research used a quantitative method where the research variables included service quality, usefulness, and satisfaction of PBG applicants towards SIMBG. The population and sample of the study were selected using accidental sampling method, with a total sample of 99 respondents. Data analysis method used Structural Equation Modeling (SEM) with SmartPLS 4.0 application. The results showed that the service quality of SIMBG has a significant influence on the satisfaction of PBG applicants and there is a positive influence between the usefulness of the SIMBG application and the satisfaction of PBG applicants. Several steps are needed: firstly, it is necessary to improve the quality of SIMBG services by improving system reliability, application responsiveness, and service politeness. Second, intensive socialization and education to the public about the existence and benefits of the SIMBG application are needed. And third, the management of PBG requirements needs to be simplified by adopting a one-stop approach to facilitate the application process. Finally, continuous evaluation and monitoring are needed to evaluate the implementation and quality of SIMBG services and to address ongoing PBG issues.